COMPARATIVE ASSESSMENT OF PUBLIC HEALTH EMERGENCY SUPPLY CHAIN AND PHARMACEUTICAL PREPAREDNESS IN PLATEAU AND NASARAWA STATES, NIGERIA, BENCHMARKED AGAINST FEDERAL STANDARDS - James Soujah Abu; Abah Michael Idoko; Adamu Ishaku Akyala; Vincent-Vera Okwosa; Olasunkanmi Samson Coker; Onojah Matthew (INTERNATIONAL JOURNAL OF PUBLIC HEALTH RESEARCH AND DEVELOPMENT, 2026)
Subnational health systems in Nigeria are central to public health emergency response, yet comparative, indicator-based evidence on state-level supply chain and pharmaceutical preparedness remains limited. This study compared emergency supply chain and pharmaceutical preparedness in Plateau and Nasarawa States, Nigeria, and benchmarked Nasarawa State against federal preparedness standards. A comparative, indicator-based assessment was conducted using administrative records, logistics management information system (LMIS) reports, emergency preparedness documents, standard operating procedures (SOPs), and warehouse assessments obtained from the Plateau and Nasarawa State Ministries of Health and associated emergency management agencies, covering the period 2020–2025. Indicators spanned institutional planning documents, cold chain and transport infrastructure, staffing, and response times for COVID-19, Lassa fever, and flood emergencies (Plateau vs Nasarawa), pharmaceutical supply chain performance (stock-out rates, buffer stock compliance, distribution times, LMIS reporting, wastage), and a set of ten federal-versus-Nasarawa State benchmarking indicators. Group comparisons for pharmaceutical indicators were tested using chi-square and independent-samples t-tests. Plateau State outperformed Nasarawa State across all institutional capacity indicators assessed, including cold chain coverage (82.4% vs 69.2% of LGAs), emergency stock availability (65.3% vs 51.7% of facilities), trained logistics staff (81.8% vs 60.0%), and response times for COVID-19 (48 vs 72 hours), Lassa fever (36 vs 60 hours), and flood emergencies (52 vs 84 hours). Pharmaceutical supply chain performance was significantly better in Plateau State across all seven indicators assessed, including emergency stock-out rate (18.4% vs 31.2%, χ²=24.7, p